Clinical features of migraine with aura: a REFORM study - Thomsen, Andreas Vinther; Ashina, Håkan; Al-Khazali, Haidar M.; Rose, Kathrine; Christensen, Rune Häckert; Amin, Faisal Mohammad; Ashina, Messoud (Journal of headache and pain, 2024)
Background About one-third of persons with migraine experience transient neurologic symptoms, referred to as aura. Despite its widespread prevalence, comprehensive clinical descriptions of migraine with aura remain sparse. Therefore, we aimed to provide an in-depth phenotypic analysis of aura symptoms and characteristics in a cross-sectional study of a large sample of adults diagnosed with migraine with aura. Methods Data were extracted from the baseline characteristics of participants in the Registry for Migraine (REFORM) study – a single-center, prospective, longitudinal cohort study. Participants were adults diagnosed with migraine aura, reporting ≥ 4 monthly migraine days in the preceding 3 months. Trained personnel conducted in-person semi-structured interviews, capturing details on the nature, duration, localization, and progression of individual aura symptoms. Results Of the 227 enrolled participants with migraine with aura, the mean age was 41.1 years, with a predominant female representation ( n = 205 [90.3%]). Visual aura was present in 215 (94.7%) participants, somatosensory aura in 81 (35.7%), and speech and/or language aura in 31 (13.7%). A single type of aura was observed in 148 (65.2%) participants, whilst 79 (34.8%) reported multiple aura types. Most participants ( n = 220 [96.9%]) described their aura symptoms as positive or gradually spreading. Headache in relation to aura was noted by 218 (96.0%) participants, with 177 (80.8%) stating that the onset of aura symptoms preceded the onset of headache. Conclusions This study offers a detailed clinical depiction of persons with migraine with aura, who were predominantly enrolled from a tertiary care unit. The findings highlight potential gaps in the available literature on migraine with aura and should bolster clinicians’ acumen in diagnosing migraine with aura in clinical settings.